Confinement effects in laminar swirling jets. (25th August 2022) - Douglas, Christopher M.; Lesshafft, Lutz
Abstract: Abstract : This paper explores the effect of axial and radial confinement on the flow topology of laminar swirling jets. Its objective is to provide a unifying perspective toward swirling jet mechanics that connects earlier reports across a variety of confined and unconfined flow situations, and over a range of swirl ratio $S$ values. The analysis focuses separately on the influence of the jet's injection depth $L$ in a radially unconfined flow and of the chamber diameter $C$ in radially confined jets. In the former case, it shows that axial confinement influences strongly the jet's behaviour when $L$ is small, allowing bistable steady states: a central jet (CJ) solution with or without a small central recirculation zone (CRZ), and a wall jet (WJ) solution with a wide-open CRZ spreading along the reservoir's edge. Similar behaviour is identified for radially confined jets, where bistable CJ and WJ states appear over a range of moderate $C$ values, and the WJ state adopts a conical CRZ. In either case, the WJ solution appears or disappears via saddle–node bifurcations when the confinement is made sufficiently strong or weak, respectively. This dynamics is attributed to an exchange of dominance between central and outer low-pressure regions as the flow transitions from CJ to WJ, or vice versa. The findings demonstrate that the hysteresis associated widely with swirling jets is controlled not just by vortex breakdown, but also by confinement through the Coandă effect. Such confinement is found to alter significantly the state-space structure even when the walls are far from the nozzle.